Pemikiran Filsafat Islam Jawa Damardjati Supadjar - Muhammad Sunandar Alwi (JURNAL INDO-ISLAMIKA, 2020)
This article discusses the thoughts, methods, origins, and influences of Javanese Islamic philosophical thought Damardjati Supadjar. Born in Losari Village, Grabag District, Magelang Regency, March 30, 1940 died 17 February 2014 in Sleman Yogyakarta. The method of thinking is: unique, operational, and testified. The origin and influence of the philosophy of the process were greatly influenced by Whitehead, who developed himself by Damardjati Supadjar who became an (othak-athik gathuk) philosophy. Damardjati Supadjar thoughts about Javanese Islamic philosophy can be seen from the view of nature as sangkan paraning dumadi, which is about the origin and purpose of everything in the universe that comes from God and returns to Him. Humans as khalifatullah mongko ojo dumeh (forbidden from acting arbitrarily). In divinity there is sarira batara (kawula-gusti), that is, humans are only kumawula (servants) who have to melt in the leprosy (God). Then education is ngelmu iku kalakone kanthi laku behavior when the intention to get knowledge must be lived through behavior (the process of seeking knowledge). While morality is critical thinking on the basis of the teaching of acting to be a good human being.